Extended calculations of energy levels, radiative properties, AJ, BJ hyperfine interaction constants, and Landé gJ-factors for nitrogen-like Ge XXVI. (March 2018) - Wang, K.; Zhang, C.Y.; Jönsson, P.; Si, R.; Zhao, X.H.; Chen, Z.B.; Guo, X.L.; Chen, C.Y.; Yan, J.
Highlights: Energies, transition rates, hyperfine interaction constants, and Landé g J -factors of the lowest 272 levels in Ge XXVI are provided. The MCDHF and MBPT methods are employed. The most accurate and complete atomic data in Ge XXVI are provided to date. Abstract: Employing two state-of-the-art methods, multiconfiguration Dirac–Hartree–Fock and second-order many-body perturbation theory, highly accurate calculations are performed for the lowest 272 fine-structure levels arising from the 2 s 2 2 p 3, 2 s 2 p 4, 2 p 5, 2 s 2 2 p 2 3 l ( l = s, p, d ), 2 s 2 p 3 3 l ( l = s, p, d ), and 2 p 4 3 l ( l = s, p, d ) configurations in nitrogen-like Ge XXVI. Complete and consistent atomic data, including excitation energies, lifetimes, wavelengths, hyperfine structures, Landé gJ -factors, and E1, E2, M1, M2 line strengths, oscillator strengths, and transition rates among these 272 levels are provided. Comparisons are made between the present two data sets, as well as with other available experimental and theoretical values. The present data are accurate enough for identification and deblending of emission lines involving the n = 3 levels, and are also useful for modeling and diagnosing fusion plasmas.